Management of Dystocia through Subcutaneous Fetotomy in Holstein Friesian Cow: A Case Report - Yadav, Vishal; Kumar, Pramod; Dholpuria, Sandeep; Sharma, Pawan Kumar; Pooja, (The Indian Journal of Animal Reproduction, 2022)
A successful delivery of dead fetus with right lateral deviation of head and neck in Holstein Friesian cow and its management through subcutaneous fetotomy is reported. Post-operative care compromised of administration of antibiotics, anti-inflammatory, ecobolic drugs along with supportive therapy.
Keywords: Dystocia; Holstein Friesian cow; Subcutaneous fetotomy